2014
DOI: 10.3174/ajnr.a4045
|View full text |Cite
|
Sign up to set email alerts
|

Forced Arterial Suction Thrombectomy with the Penumbra Reperfusion Catheter in Acute Basilar Artery Occlusion: A Retrospective Comparison Study in 2 Korean University Hospitals

Abstract: BACKGROUND AND PURPOSE:A performance of forced arterial suction thrombectomy was not reported for the treatment of acute basilar artery occlusion. This study compared revascularization performance between intra-arterial fibrinolytic treatment and forced arterial suction thrombectomy with a Penumbra reperfusion catheter in patients with acute basilar artery occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
1
18
1
Order By: Relevance
“…Procedural time is attributed to the reduction of the OTR. In our study, the mean procedural time was 39 (median 25) min, which is shorter than that in other studies [5,6,8,9,31,32.] This was also shorter than the mean procedural time of 48 min of BAO for anterior circulation at our facility.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Procedural time is attributed to the reduction of the OTR. In our study, the mean procedural time was 39 (median 25) min, which is shorter than that in other studies [5,6,8,9,31,32.] This was also shorter than the mean procedural time of 48 min of BAO for anterior circulation at our facility.…”
Section: Discussioncontrasting
confidence: 50%
“…However, a higher recanalization rate and more favorable outcomes than IVT or intra-arterial thrombolysis (IAT) have been reported, suggesting that MT may be an innovative therapy for BAO [5,6,7]. Stent retrievers and the Penumbra system are mostly used as a device in MT [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Evidence of endovascular treatment for posterior circulation occlusions is still lacking, though a few recent studies have shown better clinical outcomes compared with previous results. 9,10 Underlying stenosis due to intracranial atherosclerotic disease (IAD) is often encountered during endovascular treatment for acute intracranial large-artery occlusion. Regarding the pathomechanism of stroke, in situ thrombotic occlusions may occur in addition to hemodynamic compromise due to stenosis.…”
mentioning
confidence: 99%
“…Using this type of catheter has shown improvements in recanalization rates and favorable clinical outcomes as stent retriever thrombectomy 12)17)18). Although contrast leakage and subarachnoid hemorrhage (SAH) have been reported during and after MAT, pseudoaneurysm formation due to vessel wall injury has not been 2)6)7)8)9)10)11)12)13)14)15)17)18). We therefore report on a case of significant contrast leakage during MAT in which we found pseudoaneurysm formation at follow-up angiogram that was treated by detachable coil embolization.…”
Section: Introductionmentioning
confidence: 94%